Balloon-occluded transcatheter arterial chemoembolization for hepatocellular carcinoma - Hatanaka, Takeshi (World J Hepatol, 2018)
Transcatheter arterial chemoembolization (TACE) is widely accepted as a treatment for patients with hepatocellular carcinoma (HCC) in the intermediate stage according to the Barcelona Clinic Liver Cancer (BCLC) guidelines. Recently, balloon-occluded TACE (B-TACE) was developed in Japan. Despite the lack of a clear definition, B-TACE is generally defined as the infusion of emulsion of chemotherapeutic agents with lipiodol followed by gelatin particles under the occlusion of feeding arteries by a microballoon catheter, which leads to the dense lipiodol emulsion (LE) accumulation in HCC nodules. This phenomenon cannot be explained only by the prevention of proximal migration and leakage of embolization materials; it further involves causing local changes in the hemodynamics of the surrounding occlusion artery and targeted HCC nodules. Balloon-occluded arterial stump pressure plays an important role in the dense LE accumulation in targeted HCC nodules. Although randomized controlled trials comparing the therapeutic effect and the prognosis of B-TACE to those of the other TACE procedures, such as conventional-TACE and drug-eluting beads TACE, are still lacking, B-TACE is thought to be a promising treatment. The purpose of this review is to summarize the mechanism, therapeutic effect, indication, prognosis and complications of B-TACE.